Econometric modelling of foreign direct investment in the ASEAN economies. - Peh, Chee Kin. (2011)
In the past, although foreign direct investment (FDI) determinants have been studied extensively, there are few FDI studies that focus solely on the ASEAN nations. Furthermore, a number of these studies are plagued by methodological deficiencies. These compelling reasons motivate the need for this study. The question to be addressed by this study concerns not only on how different host country characteristics affect the locational decisions of overseas investment, but also to address the research deficiencies of previous studies. Therefore in this study, we will assess three previous studies, and also specifically focus on five ASEAN Member countries — Indonesia, Malaysia, Philippines, Singapore, and Thailand — in order to identify the FDI determinants of these nations.